MANAJEMEN DANA BOS DALAM PERSPEKTIF GOOD GOVERNANCE (STUDI KASUS SMPN 1 DAN SMPN 9 TIDORE KEPULAUAN) - Ilyas, Isran (HOLISTIK, Journal Of Social and Culture, 2013)
The budget of School Operational Grant (Bantuan Operasional Sekolah-BOS) is gools to make free educational budget for the poor students and to make easy for another students. To implementing this program at schools with good implementing is need a manajemen based to good governance principels. It meants the schools and parents of students together with School commite participate in program implementing beginning from planning, implementing and monitoring.Â  The gools of this risert is to know how to managing School Operational Grant in good governance perspecrive (study cassus) at SMP Negeri 1 dan SMP Negeri 9 Tidore Kepulauan. The result of this risert is swows that manajemen of School Operational Grant at SMP Negeri 1 and SMP Negeri 9 Tidore Kepulauan are not optimal yet. To be able to get School Operational Grant manajemen with good governance perspective, it shall entangling the society in make planning, implementing and evaluation.Keywords: budget, good governance, implementation